Protecting Intestinal Microenvironment Alleviates Acute Graft-Versus-Host Disease - Zhou, Zhengcan; Shang, Ting; Li, Xiurong; Zhu, Hongyan; Qi, Yu-Bo; Zhao, Xin; Chen, Xi; Shi, Zhe-Xin; Pan, Guixiang; Wang, Yue-Fei; Fan, Guanwei; Gao, Xiumei; et al. (Frontiers in Physiology, 2021)
Acute gut graft-vs.-host disease (GVHD) is a leading threat to the survival of allogeneic hematopoietic stem cell transplantation (allo-HSCT) recipients. Abnormal gut microbiota is correlated with poor prognosis in allo-HSCT recipients. A disrupted intestinal microenvironment exacerbates dysbiosis in GVHD patients. We hypothesized that maintaining the integrity of the intestinal barrier may protect gut microbiota and attenuate acute GVHD. This hypothesis was tested in a murine acute GVHD model and an in vitro intestinal epithelial culture. Millipore cytokine array was utilized to determine the expression of pro-inflammatory cytokines in the serum. The 16S rRNA sequencing was used to determine the abundance and diversity of gut microbiota. Combining Xuebijing injection with a reduced-dose of cyclosporine A (CsA) is superior to CsA alone in improving the survival of aGVHD mice and delayed aGVHD progression. This regimen also reduced IL-6 and IL-12 levels in the peripheral blood. 16s rRNA analysis revealed the combination treatment protected gut microbiota in aGVHD mice by reversing the dysbiosis at the phylum, genus, and species level. It inhibited Enterococcal expansion, a hallmark of GVHD progression, and worse outcomes related to allo-HSCT. Furthermore, Escherichia coli expansion was inhibited by this regimen. Pathology analysis revealed that the combination treatment improved the integrity of the intestinal tissue of aGVHD mice. It also reduced the intestinal permeability in aGVHD mice. Besides, XBJ ameliorated Doxorubicin-induced intestinal epithelial death in CCK-8 assay. Overall, Combining XBJ with CsA protected the intestinal microenvironment to prevent aGVHD. Our findings suggested that protecting the intestinal microenvironment could be a novel strategy to manage aGVHD. Combining XBJ with CsA may reduce the side-effects of current aGVHD prevention regimens and improve the quality of life of allogeneic hematopoietic stem cell transplantation recipients.